Using English Speaking MoviestoEnhanceEFL TeachingAspects. Case Study of Middle SchoolClasses at Laghouat - Merigui, Meriem; Koreichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2018)
For many years, finding ways and materials to make the English Language learning process for students more effective and inspiring has been one of the most important tasks of teaching English. It becomes very popular among teachers of English to use movies or short videos, as core content in the course curriculum or supplementary materials to teach English. For that reason, many researchers claimed that authentic source is very motivating and beneficial. The present study sheds light on the impact of using English movies as a medium to enhance teaching English language for middle school classes in Laghouat. For this purpose, a questionnaire for the teachers of the middle school classes has been conducted. The teachers’ questionnaire constitutes of eleven questions used to know whether English speaking movies are effective in improving teaching EFL or not. Through the analysis of the data collected, it is noticed that the teachers consider movies as an essential technique in enhancing their teaching of the listening skill, including pronunciation, and enriching their vocabulary. In addition to that, the findings show that movies increase the students motivation to know more about this language and develop the achievement of English language